GEOSYNTHETIC REACTIVE CLAY (GRC) HAVING AN ATTAPULGITE CLAY CORE FOR THE CAPPING OR CONTAINMENT OF CONTAMINATED SOIL - KOLLIOS, Anastasios; ZOTIADIS, Vasileios (2018)
Geosynthetic Reactive Clay (GRC) comprising a core of attapulgite clay for the capping/containment of contaminated soil. The new Geosynthetic Reactive Clay has a thickness of 8-12 mm and consists of a granular, hydraulically permeable, attapulgite clay, attapulgite/saponite clay, thermally modified or unmodified, sandwiched between two woven-non-woven geotextiles. The new geocomposite presents hydraulic "active"-filter function, i.e. it allows unobstructed passage of water while it functions as a geochemical barrier for a wide range of contaminants. The field of applications of the geocomposite regards capping and/or containment of contaminated soil. The production method of the new geocomposite comprises layering of the attapulgite clay on the first non-woven geotextile (base), while water is sprayed for better adhesion of the clay thereon and easier needle-punching of the geocomposite. Before needle-punching, the second non-woven geotextile is placed, which contains polypropylene fibers having a length larger than 9 mm. The fibers pass through the attapulgite clay and the first non-woven geotextile and remain in its lower sublayer so that the clay is retained in the geocomposite.